Microstructural characterisation of As-Cast Binary near gamma titanium aluminides - Hamzah, Esah; Kanniah, Maiiyeaalagan; Harun, Mohd. (Penerbit UTM Press, 2005)
Intermetallics Based On Ti-Al Compounds Exhibits Promising Properties For High Temperature Applications. However, Only Two Phase Near Gamma Alloys Are Able To Some Extent Fulfill The Crucial High Temperature Applications. Therefore During The Past Decade, A Number Of Research Efforts Were Directed To Optimise The Application Of This Recently Emerging Class Of Alloy. Since The High Temperature Property Which Mainly Concerns Creep Is Strongly Microstructure Dependent, A Comprehensive Understanding On The Microstructure Is Needed. In This Paper, The Current Knowledge On The Microstructures Of As-Cast Binary Near Gamma Titanium Aluminides Will Be Addressed.